THE EFFECT OF WRITING FEATURES OF GOOGLE CLASSROOM USAGE ON STUDENTS WRITING ABILITY FOR NARRATIVE TEXT MATERIALS - Idris, A. Muzkiah; Ul Haq, Muhammad Zia; Setiadi, Muhammad Astrianto (FKIP Unismuh Makassar, 2023)
The aim of this research is to find out whether the use of feature writing of Google Classroom is effective in improving students' writing ability for narrative text. the method in this research usage Quasi -experimental research which used two classes.This research method was used to process data using quantitative SPSS obtained from the results of the pre-test and post-test of the two sample classes. The participants in this study were students of Class X IPS at SMAN 6 BONE. Purposive sampling is used by the current researcher. The results of the study reveal that, it can be said that the use of writing features in the google classroom application can be used effectively to teach the competence of class X IPS students at SMAN 6 Bone.